Student’s perception towards using Quizizz as an online evaluation medium of English learning - Ota, Maria Kristina; Banda, Yosef Moan; Sama, Gratiana; Kara, Yuliana Maria D’Karmel (Univeritas Papua, 2023)
Using technology as a medium in the learning process is very beneficial for teachers, lecturers, and students. Quizizz is a web tool that can be used to conduct interactive quizzes for learning. Quizizz, in this study, is used as an online evaluation medium for learning English. However, every learning medium has advantages and disadvantages, including Quizizz. This research aims to determine students' perceptions of Quizizz as an online evaluation medium for English language learning. The mixed method is the method of this study, with the instruments being observation, questionnaires, and interviews. The research subjects were twenty students of economics education. The results obtained from the questionnaire showed that the use of Quizizz in online evaluation received positive responses from students. This response is shown by the ten questionnaire items getting a high percentage for each positive statement. Likewise, from the in-depth interviews, the data obtained also received positive and varied responses. From the results of this research, it was concluded that online evaluation using Quizizz media was very well received by students and could be used in the future by considering input and suggestions from students regarding this medium. In addition, other subjects can use this medium as a learning evaluation medium.